Analisis Kualitatif tentang Sinergi Pemerintah, Pelaku Usaha, dan Lembaga Sertifikasi dalam Pengembangan Klaster Kosmetika Halal di Indonesia - Anisa Lestari; Fahriya, Fahriya; Nurul Layali; Dian , Dian; Muhammad Ersya Faraby (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
The halal cosmetics industry in Indonesia has grown rapidly in recent years in line with the increasing awareness of Muslim consumers regarding product safety, cleanliness, and compliance with Islamic law. However, this industry still faces several challenges, particularly related to the availability of halal-certified raw materials, production process standardization, and coordination among key stakeholders. This study aims to analyze the synergy between the government, business actors, and halal certification institutions in the development of the halal cosmetics cluster in Indonesia. Using a qualitative approach and case study design, this research draws on literature analysis and applies the concepts of halal industry clusters and the triple helix model. The results indicate that collaboration among cosmetic manufacturers, government institutions, and certification bodies such as BPOM and LPPOM-MUI has strengthened consumer trust and legal assurance regarding halal products. Nevertheless, barriers remain, including limited knowledge among producers about halal standards and uneven support infrastructures across regions. Therefore, strengthening policy integration, capacity building for industry players, and institutional support is necessary to enhance the competitiveness and sustainability of the halal cosmetics industry in accordance with the principles of Maqashid Sharia.